Long-Run Saving Dynamics: Evidence from Unexpected Inheritances - Jeppe Druedahl; Alessandro Martinello (Lund University, School of Economics and Management, Department of Economics, 2017)
Long-run saving dynamics are a crucial component of consumption-saving behavior. This paper makes two contributions to the consumption literature. First, we exploit inheritance episodes to provide novel causal evidence on the long-run effects of a large financial windfall on saving behavior. For identification, we combine a longitudinal panel of administrative wealth reports with variation in the timing of sudden, unexpected parental deaths. We show that after inheritance net worth converges towards the path established before parental death, with only a third of the initial windfall remaining after a decade. These dynamics are qualitatively consistent with convergence to a buffer-stock target. Second, we analyze our findings through the lens of a generalized consumption-saving framework, and show that life-cycle consumption models can replicate this behavior, but only if the precautionary saving motive is stronger than usually assumed. This result also holds for two-asset models, which imply a high marginal propensity to consume.
Keywords: D14; D91; E21; G11; G40; 330; Inheritance; saving dynamics; consumption; buffer-stock; structural; causal; convergence; precautionary; retirement